Risk Factors for New Zealand Sea Lion (Phocarctos hookeri) Pup Mortality: Ivermectin Improves Survival for Conservation Management - Michael, Sarah A.; Hayman, David T. S.; Gray, Rachael; Roe, Wendi D. (Frontiers in Marine Science, 2021)
Septicaemia due to hypervirulent (HV) Klebsiella pneumoniae is the leading cause of neonatal pup mortality in endangered New Zealand sea lions (Phocarctos hookeri) at Enderby Island, in the New Zealand sub-Antarctic. Accounting for approximately 60% of annual pup mortality at this site following an epizootic event in 2001-02, HV K. pneumoniae is also emerging worldwide as a significant community-acquired human pathogen. To facilitate efficient direct mitigation to reduce pup mortality, a case control study and prospective cohort study were conducted to identify risk factors amenable to active management. Additionally, to investigate impacts of hookworm (Uncinaria spp.), a nested treatment trial with the anthelmintic ivermectin was undertaken concurrently. During two austral summer field seasons (2016-18), 698 pups were captured for treatment trial recruitment and the collection of morphometric measurements, biological samples and risk factor data. Gastrointestinal carriage of the virulent phenotype of K. pneumoniae was a consistent risk factor, while ivermectin treatment and higher body condition index consistently reduced risk of HV K. pneumoniae mortality. Significantly fewer ivermectin-treated pups were found dead (24.1% control, 11.1% treatment), with a trend towards a higher proportion of HV K. pneumoniae deaths amongst the control group. This study provides evidence to support ivermectin treatment as a pup mortality mitigation strategy in New Zealand sea lions at Enderby Island. If applied to larger colonies where HV K. pneumoniae and hookworm impact pup survival, this intervention could have population-scale benefits for this endangered species. Further work is required to understand how ivermectin prevents HV K. pneumoniae septicaemia, but removal of hookworms before intestinal mucosal damage occurs could limit systemic spread of virulent bacteria from the gastrointestinal tract.